Mesangial cell α(v)β(8)-integrin regulates glomerular capillary integrity and repair - Lakhe-Reddy, Sujata (American Physiological Society, 2014)
α(v)β(8)-Integrin is most abundantly expressed in the kidney, brain, and female reproductive organs, and its cognate ligand is latent transforming growth factor (LTGF)-β. Kidney α(v)β(8)-integrin localizes to mesangial cells, and global β(8)-integrin gene (Itgb8) deletion results in embryonic lethality due to impaired placentation and cerebral hemorrhage. To circumvent the lethality and better define kidney α(v)β(8)-integrin function, Cre-lox technology was used to generate mesangial-specific Itgb8-null mice. Platelet-derived growth factor-β receptor (PDGFBR)-Cre mice crossed with a reporter strain revealed functional Cre recombinase activity in a predicted mesangial pattern. However, mating between two different PDGFBR-Cre or Ren1(d)-Cre strains with Itgb8 (flox/−) mice consistently resulted in incomplete recombination, with no renal phenotype in mosaic offspring. Induction of a renal phenotype with Habu snake venom, a reversible mesangiolytic agent, caused exaggerated glomerular capillary microaneurysms and delayed recovery in Cre(+/−) PDGFRB (flox/−) mice compared with Cre(+/−) PDGFRB (flox/+) control mice. To establish the mechanism, in vitro experiments were conducted in Itgb8-null versus Itgb8-expressing mesangial cells and fibroblasts, which revealed β(8)-integrin-regulated adhesion to Arg-Gly-Asp (RGD) peptides within a mesangial-conditioned matrix as well as β(8)-integrin-dependent migration on RGD-containing LTGF-β or vitronectin matrices. We speculate that kidney α(v)β(8)-integrin indirectly controls glomerular capillary integrity through mechanical tension generated by binding RGD peptides in the mesangial matrix, and healing after glomerular injury may be facilitated by mesangial cell migration, which is guided by transient β(8)-integrin interactions with RGD ligands.